# Prove the equality:

$\underset{n\text{ digits}}{\mathop{{{\left( 666...6 \right)}^{2}}}}\,+\underset{n\text{ digits}}{\mathop{888...8}}\,=\underset{2n\text{ digits}}{\mathop{444...4}}\,$

Answer

Verified

363.6k+ views

Hint: Take ${{S}_{1}}=666...6,{{S}_{2}}=888...8$. Expand them to form a geometric progression. Then find the value of ${{S}_{1}}^{2}+{{S}_{2}}$.

“Complete step-by-step answer:”

$\begin{align}

& \text{Take }{{S}_{1}}=666...6 \\

& \text{Given }{{S}_{1}}=666...\text{upto n-digits} \\

& =6+6\times 10+6\times {{10}^{2}}+6\times {{10}^{3}}+...+6\times {{10}^{n-1}} \\

& =6\left( 1+10+{{10}^{2}}+....+{{10}^{n-1}} \right) \\

\end{align}$

Now $1+10+{{10}^{2}}+....+{{10}^{n-1}}$ is the expanded form of $\dfrac{{{10}^{n}}-1}{10-1}$

i.e., It is of the form $\dfrac{a\left( {{r}^{n}}-1 \right)}{r-1}$

Where a = first term, r = common ratio

Which is a geometric progression.

Here a = 1, r = 10.

$\therefore {{S}_{1}}=6\left[ 1\left( \dfrac{{{10}^{n}}-1}{10-1} \right) \right]=6\times \dfrac{\left( {{10}^{n}}-1 \right)}{9}=\dfrac{2}{3}\left( {{10}^{n}}-1 \right)$

Now ${{S}_{2}}=888...$ up to n-digits

\[\begin{align}

& =8+8\times 10+8\times {{10}^{2}}+...+8\times {{10}^{n-1}} \\

& =8\left( 1+10+{{10}^{2}}+...+{{10}^{n-1}} \right) \\

& =8\times 1\left[ \dfrac{{{10}^{n}}-1}{10-1} \right]=\dfrac{8}{9}\left( {{10}^{n}}-1 \right) \\

\end{align}\]

We need to find ${{\left( {{S}_{1}} \right)}^{2}}+{{S}_{2}}={{\left[ \dfrac{2}{3}\left( {{10}^{n}}-1 \right) \right]}^{2}}+\dfrac{8}{9}\left( {{10}^{n}}-1 \right)$

$\begin{align}

& =\dfrac{4}{9}{{\left( {{10}^{n}}-1 \right)}^{2}}+\dfrac{8}{9}\left( {{10}^{n}}-1 \right) \\

& =\dfrac{\left( {{10}^{n}}-1 \right)}{9}\left[ 4\left( {{10}^{n}}-1 \right)+8 \right] \\

\end{align}$

Taking 4 common,

$\begin{align}

& =4\left( \dfrac{{{10}^{n}}-1}{10-1} \right)\left[ \left( {{10}^{n}}-1 \right)+2 \right] \\

& =4\left[ \dfrac{{{10}^{n}}-1}{10-1} \right]\left[ {{10}^{n}}-1+2 \right] \\

& =4\dfrac{\left( {{10}^{n}}-1 \right)\left( {{10}^{n}}+1 \right)}{10-1} \\

& =4\dfrac{\left[ {{\left( {{10}^{n}} \right)}^{2}}-{{1}^{2}} \right]}{10-1} \\

\end{align}$

We know ${{a}^{2}}-{{b}^{2}}=\left( a+b \right)\left( a-b \right)$

$=\dfrac{4\left[ {{10}^{2n}}-1 \right]}{\left[ 10-1 \right]}$

$\therefore $444....4 up to 2n digits.

Hence proved.

Note: A geometric progression is a sequence in which each term is derived by multiplying/dividing the preceding term by a fixed number called common ratio.

The general form of GP is $a,ar,a{{r}^{2}},a{{r}^{3}}$ and so on;

a = first term

r = common ratio

“Complete step-by-step answer:”

$\begin{align}

& \text{Take }{{S}_{1}}=666...6 \\

& \text{Given }{{S}_{1}}=666...\text{upto n-digits} \\

& =6+6\times 10+6\times {{10}^{2}}+6\times {{10}^{3}}+...+6\times {{10}^{n-1}} \\

& =6\left( 1+10+{{10}^{2}}+....+{{10}^{n-1}} \right) \\

\end{align}$

Now $1+10+{{10}^{2}}+....+{{10}^{n-1}}$ is the expanded form of $\dfrac{{{10}^{n}}-1}{10-1}$

i.e., It is of the form $\dfrac{a\left( {{r}^{n}}-1 \right)}{r-1}$

Where a = first term, r = common ratio

Which is a geometric progression.

Here a = 1, r = 10.

$\therefore {{S}_{1}}=6\left[ 1\left( \dfrac{{{10}^{n}}-1}{10-1} \right) \right]=6\times \dfrac{\left( {{10}^{n}}-1 \right)}{9}=\dfrac{2}{3}\left( {{10}^{n}}-1 \right)$

Now ${{S}_{2}}=888...$ up to n-digits

\[\begin{align}

& =8+8\times 10+8\times {{10}^{2}}+...+8\times {{10}^{n-1}} \\

& =8\left( 1+10+{{10}^{2}}+...+{{10}^{n-1}} \right) \\

& =8\times 1\left[ \dfrac{{{10}^{n}}-1}{10-1} \right]=\dfrac{8}{9}\left( {{10}^{n}}-1 \right) \\

\end{align}\]

We need to find ${{\left( {{S}_{1}} \right)}^{2}}+{{S}_{2}}={{\left[ \dfrac{2}{3}\left( {{10}^{n}}-1 \right) \right]}^{2}}+\dfrac{8}{9}\left( {{10}^{n}}-1 \right)$

$\begin{align}

& =\dfrac{4}{9}{{\left( {{10}^{n}}-1 \right)}^{2}}+\dfrac{8}{9}\left( {{10}^{n}}-1 \right) \\

& =\dfrac{\left( {{10}^{n}}-1 \right)}{9}\left[ 4\left( {{10}^{n}}-1 \right)+8 \right] \\

\end{align}$

Taking 4 common,

$\begin{align}

& =4\left( \dfrac{{{10}^{n}}-1}{10-1} \right)\left[ \left( {{10}^{n}}-1 \right)+2 \right] \\

& =4\left[ \dfrac{{{10}^{n}}-1}{10-1} \right]\left[ {{10}^{n}}-1+2 \right] \\

& =4\dfrac{\left( {{10}^{n}}-1 \right)\left( {{10}^{n}}+1 \right)}{10-1} \\

& =4\dfrac{\left[ {{\left( {{10}^{n}} \right)}^{2}}-{{1}^{2}} \right]}{10-1} \\

\end{align}$

We know ${{a}^{2}}-{{b}^{2}}=\left( a+b \right)\left( a-b \right)$

$=\dfrac{4\left[ {{10}^{2n}}-1 \right]}{\left[ 10-1 \right]}$

$\therefore $444....4 up to 2n digits.

Hence proved.

Note: A geometric progression is a sequence in which each term is derived by multiplying/dividing the preceding term by a fixed number called common ratio.

The general form of GP is $a,ar,a{{r}^{2}},a{{r}^{3}}$ and so on;

a = first term

r = common ratio

Last updated date: 02nd Oct 2023

•

Total views: 363.6k

•

Views today: 7.63k

Recently Updated Pages

What do you mean by public facilities

Difference between hardware and software

Disadvantages of Advertising

10 Advantages and Disadvantages of Plastic

What do you mean by Endemic Species

What is the Botanical Name of Dog , Cat , Turmeric , Mushroom , Palm

Trending doubts

How do you solve x2 11x + 28 0 using the quadratic class 10 maths CBSE

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

What is meant by shramdaan AVoluntary contribution class 11 social science CBSE

The equation xxx + 2 is satisfied when x is equal to class 10 maths CBSE

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Difference Between Plant Cell and Animal Cell

An alternating current can be produced by A a transformer class 12 physics CBSE

What is the value of 01+23+45+67++1617+1819+20 class 11 maths CBSE

Give 10 examples for herbs , shrubs , climbers , creepers